Distal upper extremity musculoskeletal disorders in industrial workers - Siavash Dastmanesh; Seyed Sadreddin Shojaeddin (Vesnu Publications, 2011)
Introduction: The aim of this study was to evaluate distal upper extremity musculoskeletal disorders among industrial workers.  Material and Methods: A sample of 210 male subjects including 50 controls working at administrative settings and 160 subjects working as smashers, welders and drillers in Saypa Industrial Factory were selected for the present study. An integrated approach consisting of multiple observations and interviews, completing Nordic Musculoskeletal Questionnaire (NMQ) and implementing SI model was accepted for evaluation of all subjects participated in this study. Independent and Paired t tests, One Way ANOVA and TOKEY POSTHOC tests were used for statistical analysis of raw data using SPSS software version 17 (α≤ 0.05). Results: Study results revealed that the most prevalent MSDs in upper limbs were found in welding, smashing and drilling respectively. There are significant differences between the mean scores of calculated Strain Indices obtained from administrative (1.7), welding (5.6), smashing (7.2) and drilling (8.1) jobs. These scores were respectively labeled as "safe risk level" (risk level 1), "uncertain risk level" (risk level 2) and as "hazardous jobs" (risk level 4). Conclusion: Based on study results, we concluded that workers dealing with works that involves drilling stresses were more susceptible for musculoskeletal disorders. Keywords: Musculoskeletal Disorders, Strain Index Method, Industrial Workers.